Akkermansia muciniphila: The state of the art, 18 years after its first discovery - Iwaza, Rim; Wasfy, Reham Magdy; Dubourg, Grégory; Raoult, Didier; Lagier, Jean-Christophe (Frontiers in Gastroenterology, 2022)
Akkermansia muciniphila (A. muciniphila) is an anaerobic, Gram negative and mucin-degrading bacterium of the phylum Verrucomicrobia isolated in 2004 from human feces. Although it is a common resident in the human intestinal tract, it has also been detected in other anatomical sites. Genomic studies have revealed that A. muciniphila can be divided into different phylogroups with distinct metabolic properties. There is growing evidence regarding its beneficial impact on human health. Indeed, A. muciniphila is considered as a promising next-generation probiotic for treating cancer and metabolic disorders. The large-scale production of A. muciniphila is, therefore, a challenge. Beside mucin-based medium, other culture strategies have enabled its isolation. The administration of both live and pasteurized forms of A. muciniphila has shown to be promising in animal models. Alternatively, the administration of various prebiotics has also been assessed for enhancing its abundance in the human gut. Future prospects include human clinical trials, some of which are currently ongoing. This paper provides an overview of what is currently known about A. muciniphila’s phenotypical and genotypic traits, as well as its culture techniques and its connections to a number of human diseases and its potential application as an effective next generation probiotic.